1973
DOI: 10.1111/j.1471-4159.1973.tb07581.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thiamine Deficiency on the Acetylcoenzymea and Acetylcholine Levels in the Rat Brain

Abstract: Abstract— It is shown that transketolase activities in red blood cells and whole brain of normal and thiamine‐deficient rats correlate well with heart frequencies. The effect of thiamine depletion on the levels of acetylcoenzyme A (acetyl‐CoA) and acetylcholine (ACh), and on the activities of pyruvate dehydrogenase, choline acetyl‐transferase and acetylcholine esterase was studied in whole brains of thiamine‐deficient, thiamine‐supplemented ad libitum and pair‐fed rats. The concentrations of acetyl‐CoA and ACh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…In addition, our data indicate that pyruvate oxidation and energy supply were of secondary importance for ACh production in depolarized cholinergic terminals when the acetyl-CoA transfer to the synaptoplasm was activated or uninhibited (tables 1-4). A direct assessment of subsynaptosomal compartmentalization of acetyl-CoA would appear to be necessary for an estimation of its involvement in the mechanism of cholinergic pathologies [23,24]. This statement is supported by the fact that for each effector used in this study, changes in calcium-evoked ACh release were correlated with shifts in the synaptoplasmic concentration of acetyl-CoA (r = 0.98; fig.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, our data indicate that pyruvate oxidation and energy supply were of secondary importance for ACh production in depolarized cholinergic terminals when the acetyl-CoA transfer to the synaptoplasm was activated or uninhibited (tables 1-4). A direct assessment of subsynaptosomal compartmentalization of acetyl-CoA would appear to be necessary for an estimation of its involvement in the mechanism of cholinergic pathologies [23,24]. This statement is supported by the fact that for each effector used in this study, changes in calcium-evoked ACh release were correlated with shifts in the synaptoplasmic concentration of acetyl-CoA (r = 0.98; fig.…”
Section: Discussionsupporting
confidence: 66%
“…The resulting H2O2 reacts with a specifi c dye to form a pink-colored product. The color intensity at 570 nm is directly proportional to the Ach concentration in the sample (19).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Thiamin deficiency, however, was not found to have any effect on activities of the cholinergic enzymes, acetylcholine esterase (AChE) and choline acetylase (ChAc), in the adult rat brain (17). There is no report of the study on the effects of early thiamin deficiency on the cholinergic system in the developing rat brain.…”
mentioning
confidence: 80%
“…Heinrich et al also reported unaltered activities of the cholinergic enzymes in the symptomatic thiamin deficient rats (17).…”
Section: Effects Of Thiamin Deficiency During Lactationmentioning
confidence: 99%
See 1 more Smart Citation